Logistics Outsourcing Relationships Measurement, Antecedents, and Effects of Logistics Outsourcing Performance - Deepen, Jan M.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2007)
In recent years, logistics outsourcing has gained increasing importance and today is used by a large number of firms across virtually all industries worldwide. Logistics service providers have developed a wide array of services that are utilized to improve logistics processes - and mainly to cut costs.This book uses state-of-the-art scientific methods to reveal that most firms currently do not realize the full potential of logistics outsourcing. It shows the complexity of outsourcing performance and that its true drivers lie in the relationship between service providers and their customers. Through the results of a large-scale empirical survey, the book also emphasizes the importance of a firm's approach towards outsourcing: solely striving for cost reductions may be a dead end, while the often overlooked increased logistics service levels are equally important for boosting logistics performance. In the light of current outsourcing practices, this indicates substantial room for improvement for most firms.
Basic concepts -- Theoretical framework -- Antecedents and effects of logistics outsourcing performance -- Methodology and sample characteristics -- Construct operationalization -- Structural models -- Summary and results.
Keywords: Production management; Operations Management